Treatment of Rectal Cancer-Induced Disseminated Carcinomatosis of the Bone Marrow with FOLFOX plus Cetuximab and Panitumumab - Ehara, Takehito (Case Rep Oncol, 2020)
Disseminated carcinomatosis of the bone marrow (DCBM) in colorectal cancer is an extremely rare complication with a poor prognosis. Here, we report a case of DCBM due to rectal cancer successfully treated with a combination of FOLFOX and an anti-epidermal growth factor receptor (EGFR) agent. The patient was a 38-year-old man diagnosed with rectal cancer with multiple bone and para-aortic lymph node metastases complicated by disseminated intravascular coagulation (DIC). He first recovered from DIC following cotreatment with FOLOX plus cetuximab; subsequently, the second attack was successfully treated with FOLFOX plus panitumumab. His initial condition was extremely poor, but he survived with two FOLFOX plus anti-EGFR regimens and died 333 days after introduction of chemotherapy.